2020
DOI: 10.1093/cid/ciaa074
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Use of Antibiotics, Antivirals, and Hospitalizations Among Patients With Laboratory-confirmed Influenza

Abstract: Abstract Background Clinicians may prescribe antibiotics to influenza patients at high risk for bacterial complications. We explored the association between antibiotics, antivirals, and hospitalization among people with influenza. Methods A retrospective cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Prescription rates in our study were lower than or comparable to several international studies [35][36][37][38]. A recent study documented higher rates of 30-day respiratory disease readmission in influenza patients only treated with antivirals as compared to both antivirals and antibiotics, although the absolute differences in risk were low [39]. In COVID-19 patients early antibiotic prescriptions were significantly reduced from the first to second pandemic wave (from 49% to 27%, proportionally 76% and 65% of all prescriptions).…”
Section: Discussionsupporting
confidence: 46%
“…Prescription rates in our study were lower than or comparable to several international studies [35][36][37][38]. A recent study documented higher rates of 30-day respiratory disease readmission in influenza patients only treated with antivirals as compared to both antivirals and antibiotics, although the absolute differences in risk were low [39]. In COVID-19 patients early antibiotic prescriptions were significantly reduced from the first to second pandemic wave (from 49% to 27%, proportionally 76% and 65% of all prescriptions).…”
Section: Discussionsupporting
confidence: 46%
“…In addition to commonly used neuraminidase inhibitors (NAIs) such as oseltamivir, the polymerase inhibitor baloxavir is an effective newer option that provides equal or improved efficacy compared to NAIs, including in patients with high risk of complications, as well as having the added convenience of a single-dose oral regimen. 38,39 Antiviral treatment of influenza reduces disease burden and decreases both mortality and hospitalization rates, [40][41][42] particularly in patients with secondary infections leading to pneumonia. 43 Within treatment guidelines, strategies should be considered to provide high-risk individuals with antivirals pre-emptively, to ensure patients are treated within the 48-hour window and healthcare systems are not overburdened.…”
Section: Ma Ximizing the P Otential Of Influenz A Control Me A Sure Smentioning
confidence: 99%
“…However, despite covariate adjustment for many relevant patient factors and performing propensity score matching, we cannot rule out the possibility of selection bias or residual confounding. For example, our previous work identified that antibiotics have the potential to impact hospitalization rates among patients diagnosed with influenza 35 . Therefore, we performed a sub‐analysis that included antibiotics (Table A3) as a covariate.…”
Section: Discussionmentioning
confidence: 99%